2 PERBANDINGAN KETERAMPILAN MENGELOLA MARAH SISWA DENGAN STRATEGI EMOTIONAL LITERACY DAN FGD - Nurvita, Desika Nanda (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2016)
ABSTRACT The Comparison Anger Management Skills of Students with Emotional Literacy and FGD Strategies. The purpose of this research is to understand the comparison anger management skills of junior high school with emotional literacy and focus group discussion strategies intervention. This research used quasi experiment method with the pretest- posttest two treatment designs. The subjects of the research were taken from the students of grade of VII.3 and VII.5 SMPN 5 Malang with purpossive technique selection. Pretest result shows that there are twelve students have low and very low anger management score, then they were divided into two groups which consist of six students each. The first group, experiment I, with emotional literacy strategy treatment and the second group, experiment II with focus group discussion strategy treatment. The research instrument uses anger management scale. The data analyzed by using Wilxocon sign rank test to verify the improvement of anger management in each group experiment and Mann-Whitney U test to examine any differences, if any, in the effectiveness among the two treatments. The result of the analysis indicates that the two methods used shows a significant increase and there is no significant difference between the effectiveness of the two toward the managing anger skill improvement. Key words: Emotional literacy, FGD, anger management skills.